2021
DOI: 10.17269/s41997-021-00481-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fish for food and nutrition security among First Nations in Canada

Abstract: Objective To investigate the relationships between fish/seafood consumption patterns and food security status among First Nations (FN) communities in Canada. We estimated the contribution of fish/seafood to daily nutrient requirements. Barriers to traditional food (TF) access including fish were summarized. Methods Data were collected by the First Nations Food, Nutrition and Environment Study (2008–2018). The sample of this participatory study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…First Nations living on-reserve experience extremely high rates of food insecurity: an average of 48% (range between 24% and 60%) of households are food insecure, and the rate is 3 to 5 times higher than the food insecurity rate reported for the general Canadian population (12%) (Batal et al 2021d). Fish harvest and consumption were found to be important contributors to nutritional health and food security among First Nations (Marushka et al 2021a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First Nations living on-reserve experience extremely high rates of food insecurity: an average of 48% (range between 24% and 60%) of households are food insecure, and the rate is 3 to 5 times higher than the food insecurity rate reported for the general Canadian population (12%) (Batal et al 2021d). Fish harvest and consumption were found to be important contributors to nutritional health and food security among First Nations (Marushka et al 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…The lessons learned from the Study and the significance of the results are discussed. Detailed methods and findings for each component are presented in the accompanying papers in this Special Issue of the Canadian Journal of Public Health (Batal et al 2021a-e;Marushka et al 2021aMarushka et al , 2021bChan et al 2021;Tikhonov et al 2021;andSchwartz et al 2021a, 2021b).…”
Section: Résumémentioning
confidence: 99%
“…Additional research is needed to better assess mercury exposure among First Nations men. Continued mercury biomonitoring is essential, particularly due to the importance of fish in the traditional diet of First Nations in Canada (Marushka et al, 2021). lection methodology by Iouri Romachine, PhD.…”
Section: Discussionmentioning
confidence: 99%
“…| 5 COMMENTARY income, food security, and cultural value to communities in the region (Johnson et al, 2019;Marushka et al, 2021). If historic logging has strongly reduced salmonid productivity throughout the temperate rainforest, as Wilson et al (2021) found in their study area, then new approaches to forest management could potentially yield major gains toward recovering fish populations and fisheries.…”
mentioning
confidence: 95%